Specific markers and properties of synovial mesenchymal stem cells in the surface, stromal, and perivascular regions - Mitsuru Mizuno; Hisako Katano; Yo Mabuchi; Yusuke Ogata; Shizuko Ichinose; Shizuka Fujii; Koji Otabe; Keiichiro Komori; Nobutake Ozeki; Hideyuki Koga; Kunikazu Tsuji; Chihiro Akazawa; et al. (Stem Cell Research & Therapy, 2018)
Abstract Background Synovial mesenchymal stem cells (MSCs) are an attractive cell source for cartilage and meniscus regeneration. Synovial tissue can be histologically classified into three regions; surface, stromal and perivascular region, but the localization of synovial MSCs has not been fully investigated. We identified markers specific for each region, and compared properties of MSCs derived from each region in the synovium. Methods The intensity of immunostaining with 19 antibodies was examined for surface, stromal, and perivascular regions of human synovium from six osteoarthritis patients. Specific markers were identified and synovial cells derived from each region were sorted. Proliferation, surface marker expression, chondrogenesis, calcification and adipogenesis potentials were compared in synovial MSCs derived from the three regions. Results We selected CD55+ CD271− for synovial cells in the surface region, CD55− CD271− in the stromal region, and CD55− CD271+ in the perivascular region. The ratio of the sorted cells to non-hematopoietic lineage cells was 5% in the surface region, 70% in the stromal region and 15% in the perivascular region. Synovial cells in the perivascular fraction had the greatest proliferation potential. After expansion, surface marker expression profiles and adipogenesis potentials were similar but chondrogenic and calcification potentials were higher in synovial MSCs derived from the perivascular region than in those derived from the surface and stromal regions. Conclusions We identified specific markers to isolate synovial cells from the surface, stromal, and perivascular regions of the synovium. Synovial MSCs in the perivascular region had the highest proliferative and chondrogenic potentials among the three regions.